Original paperPrevalence of IgE-mediated allergy and evaluation of Th1/Th2 cytokine profiles in patients with severe bronchial asthma - Rogala, Barbara; Bozek, Andrzej; Gluck, Joanna; Jarzab, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : The pathogenesis of asthma remains unclear, especially in cases of the severe disease. Aim : To explore IgE-mediated inhalant sensitization in severe asthma compared with a group of patients with chronic mild disease and evaluate the Th1/Th2 cytokine profiles in asthma by different disease severities. Material and methods: One hundred and fifty-four patients (age range: 28–69) with severe chronic asthma (study group) and 141 patients with chronic mild disease (control group) diagnosed according to GINA criteria were included in the study. Seventy-eight severe asthmatics and 43 subjects with mild disease were randomly selected for serum Th1/Th2 cytokine level estimation. The groups were matched in terms of age and atopy features (skin prick tests, specific and total serum IgE). Results: Positive skin tests to at least one allergen were observed with comparable frequencies. Sensitization to Dermatophagoides pteronyssinus was the most prevalent positive result in both groups. An earlier onset of asthma together with a greater number of exacerbations was noted in severe asthmatics compared to patients with mild disease. Serum levels of interleukin 4 and 2 (IL-4 and IL-2) were detectable only in severe asthmatics irrespective of atopy features. The levels of interferon γ and tumour necrosis factor α were undetectable in both groups. IL-10 and IL-5 were detected in the serum of only 7 and 12 severe asthmatics, respectively. Conclusions : The serum level of IL-2 and IL-4 could be perceived as a marker of severe asthma. Neither IL-2 nor IL-4 levels in the serum could differentiate allergic and non-allergic asthma.